2015
DOI: 10.1007/s40519-015-0206-z
|View full text |Cite
|
Sign up to set email alerts
|

The Polish version of the Body Image Avoidance Questionnaire: an exploratory structural equation modeling approach

Abstract: The objective of the study was to validate a Polish version of the Body Image Avoidance Questionnaire (BIAQ). The study included 115 participants with no diagnosis (control group) (Mage = 20.53, SD = 1.80) on which we have based factor analyses, 48 participants diagnosed with anorexia nervosa (Mage = 18.69, SD = 3.52) and 39 participants diagnosed with bulimia nervosa (Mage = 22.28, SD = 3.80). In the current study, we have run confirmatory factor analysis; however, the analysis did not fit the data (CFI = 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Cronbach’s alpha reliability coefficient for the subscale “consumption desire” used in the study was .62 (excessive body weight: .63, normal body weight: .61). Body Image Avoidance Questionnaire (BIAQ) [ 26 , 41 ] consists of four subscales: clothing and appearance (example: “I wear baggy clothes”), physical appearance (example: “I wear clothes that will divert attention from my weight”), social activities (example: “I do not go out socially if the people I am with will discuss weight”), food and weight preoccupation (example: “I restrict the amount of food I eat”). Cronbach’s alpha coefficient for the subscale “social activity” used in the conducted studies (avoidance of social situations related to food and body exposure) was .90 (excessive body weight: .92, normal body weight: .86).…”
Section: Methodsmentioning
confidence: 99%
“…Cronbach’s alpha reliability coefficient for the subscale “consumption desire” used in the study was .62 (excessive body weight: .63, normal body weight: .61). Body Image Avoidance Questionnaire (BIAQ) [ 26 , 41 ] consists of four subscales: clothing and appearance (example: “I wear baggy clothes”), physical appearance (example: “I wear clothes that will divert attention from my weight”), social activities (example: “I do not go out socially if the people I am with will discuss weight”), food and weight preoccupation (example: “I restrict the amount of food I eat”). Cronbach’s alpha coefficient for the subscale “social activity” used in the conducted studies (avoidance of social situations related to food and body exposure) was .90 (excessive body weight: .92, normal body weight: .86).…”
Section: Methodsmentioning
confidence: 99%
“…BIAQ has a factorial structure: (1) Clothing and appearance (CLO-APP), (2) Social activity (SOC-ACT), (3) Concentration on food and body weight (FO-WEI), (4) Preoccupation with physical appearance (PHYS-APP). In Polish studies ( 44 ), the questionnaire showed excellent internal consistency (Cronbach's alpha = 0.89), and the test-retest ratio was 0.87.…”
Section: Methodsmentioning
confidence: 95%
“…The last of the tools used was the Body Image Avoidance Questionnaire (BIAQ) by Rosen et al ( 43 ) in the Polish adaptation by Brytek-Matera and Rogoza ( 44 ). The BIAQ consists of 19 items, and the participant's task is to refer to them on a scale from 5 (“always”) to 0 (“never”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, it might also be that methodological issues of the BA self-report tool account for the lack of associations in ED. We used the BIAQ that has been developed in student samples and whose original structure has not been replicated in several studies (Legenbauer et al, 2007;Campana et al, 2013;Brytek-Matera and Rogoza, 2016). It has to be considered that within the German version, the original factor structure had not been replicated and that items in relation to eating loaded on a factor that reflects rather control than avoidance (Legenbauer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%